2012
DOI: 10.1002/anie.201201568
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Cross‐Linked Polymeric Binder for High‐Performance Silicon Negative Electrodes in Lithium Ion Batteries

Abstract: Electrode designs, which can accommodate severe volume changes (ca. 400 %) of silicon anode materials upon lithium insertion, are the main prerequisite for high-performance lithium ion batteries. Among various techniques investigated for this purpose, a robust polymeric binder is a promising means to inhibit mechanical fracture of silicon negative electrodes during cycling.Lithium ion batteries (LIBs) are one of the most promising energy storage devices owing to their high power and energy densities. [1] For L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
618
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 689 publications
(633 citation statements)
references
References 37 publications
14
618
0
1
Order By: Relevance
“…Our group reported a thermally cured polymeric binder as an immediate technological solution for Liion batteries with Si-based electrodes [7]. A threedimensionally interconnected network of PAA and sodium carboxymethyl cellulose (Na-CMC) as a binder was used and a nano-sized silicon anode with this crosslinked binder displayed a high Li extraction capacity that exceeded 2000 mAh g -1 after 100 cycles at 30 o C. The crosslinked polymeric binder (Fig.…”
Section: Crosslinked Polymeric Bindersmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group reported a thermally cured polymeric binder as an immediate technological solution for Liion batteries with Si-based electrodes [7]. A threedimensionally interconnected network of PAA and sodium carboxymethyl cellulose (Na-CMC) as a binder was used and a nano-sized silicon anode with this crosslinked binder displayed a high Li extraction capacity that exceeded 2000 mAh g -1 after 100 cycles at 30 o C. The crosslinked polymeric binder (Fig.…”
Section: Crosslinked Polymeric Bindersmentioning
confidence: 99%
“…Cross-linked PAA-CMC (c-PAA-CMC) binder formed by condensation between PAA and CMC. Because the OH moieties of the SiO 2 native layer on the Si surface can react with the COOH groups of PAA in a cross-linked binder, chemical binding between Si nanoparticles and c-PAA-CMC is produced [7]. ume change.…”
Section: Crosslinked Polymeric Bindersmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In particular, binders containing hydroxyl substituents on the backbone, such as polyarcrylic acid (PAA) and carboxymethyl cellulose (CMC), have been reported to have chemical bonding between binder and silicon, ensuring stronger adhesion. [20][21][22][23] Efforts to stabilize the large surface area of nano-structured silicon electrodes have utilized electrolyte additives such as fluoroethylene carbonate (FEC) and vinylene carbonate (VC) which lead to the generation of a more effective SEI. [24][25][26][27][28][29][30] * Electrochemical Society Active Member.…”
mentioning
confidence: 99%
“…Even though it was shown that nano-sized silica is electrochemically active, 40 the results show that the silicon oxide layer at the surface does not provide any benefits to the capacity, but helps in interacting with the binder and other electrode components. 41,42 Our previous results show that ball milling leads to amorphization of crystalline silicon; however, in silicon nanoparticle the amorphization did not improve reversible capacity. The nano-sized silicon might be small enough that amorphization is not required.…”
mentioning
confidence: 92%